Contribution to the Physicochemical and Microbiological Study of Dried Mango. Comparison of Two Drying Methods (Oven and Solar Drying) - Izaora Mwamba; Jean-Noel Mputu (Current Overview on Science and Technology Research Vol. 1, 2022)
Drying is one of the oldest methods of preservation processes available to the mankind. On that, we can track since prehistoric times. Food market dried foods play an important role in the food supply chain. As for fruits and vegetables it can be estimated that they constitute about 1% of the total drying in the food industry, by large being the grains the most important. The main feature of this process consists on lowering the water content in order to avoid or slow down food spoilage by microorganism. At this point some understanding can arise derived from the vocabulary employed; common words found are (drying) or (dehydration). A variety of mangoes were dried using two methods (solar and oven). The drying yield for sun-dried mango is 33%, compared to 26% for oven-dried mango; the relative humidity for sun-dried mango is 14.17% ± 0.01 versus 8.25% ± 0.01 for oven-dried mango. When compared to oven-dried mango, a reduction in dry matter is seen. The mango that has been dried in the sun contains a lot of vitamin B6, vitamin C, and minerals (Ca, Mg and Fe). But following the drying procedures, we also noticed the presence of vitamins (A, D, and E). We achieved results that adhered to the ISO 4833 standard, which controls the microbiology of the food chain, with regard to the microbiological criteria.